The effectiveness of socialization models of social life skill modules for kindergarten teachers - Yulia Ayriza (LPPM UNY, 2010)
The social life skill has not been considered important in education that makes many people from children to youngsters nowadays have more conflicts due to some very simple reasons. This study was the third phase of a three-year-research. This third year study was aimed at socializing the social life skill modules and testing three kinds of socialization models to find out which one was the most effective: the centralistic model, the chaining model, or the professional organization model. This study used the quantitative research approach with a quasi experiment as the research method. The participants were 109 kindergarten teachers in Daerah Istimewa Yogyakarta (DIY). The instruments were a questionnaire and a test, and the techniques of data analysis were quantitative description and analysis of variance. The analysis results showed: (1) The social life skill modules had been socialized among kindergarten teachers in DIY; all preschool teachers had got the modules through the three kinds of socialization models. (2) There were no differences of effectiveness among the three socialization models